Johor, 1855-1957 local history, local landscapes - Lim, Patricia Pui Huen (Think City Sdn Bhd, 2020)
How Johor was transformed from virgin jungle into a vigorous economy and a harmonious society, and how Johor Bahru grew from a village on the shoreline into a bustling metropolis - that is the story of Johor told in this book. Visionary leadership and the energy and enterprise of many people kept Johor a step ahead - whether as the world's largest producer of pepper and gambier, or as Malaya's largest rubber producer, or in the forging of the first state constitution, not to mention its leadership role in the struggle for independence. Johor was modern in its policies and multicultural in its outlook. The story of Johor is told through old photographs and historical maps accumulated through careful archival research, fieldwork through the highways and byways of Johor, and through the lives and memories of many people. It is a history of the interaction of people and landscape that has come together to make what Johor is today.